Analysis of Vitreous Samples by the Cellient® Automated Cell Block System: A Six-year Review of Specimens in a Uveitis Population. (19th May 2022) - Jacobs, Tine; Thal, Dietmar Rudolf; Weynand, Birgit; Van Calster, Joachim; Van Ginderdeuren, Rita
ABSTRACT: Purpose: To further evaluate the value of a standardized method to analyze vitreous samples using the Cellient® automated cell block system in the diagnosis of unsolved uveitis. Methods: Six hundred sixty-four pure vitreous samples obtained from patients with unsolved uveitis between March 2012 and May 2018 at University Hospitals Leuven, fixed in PreservCyt® and processed by the Cellient tissue processor, were included in the study. Results: n 86.3% of the cases, sufficient material was found for diagnosis. A diagnosis of acute inflammation was made in 20.2% of the cases. In 34.0% of the cases, the diagnosis was chronic active inflammation; in 26.5%, low-grade inflammation; and in 5.6%, a malignant process. Conclusion: Our standardized protocol can be used to diagnose endophthalmitis, lymphoma, granulomatous disease, inactive and storage disease, and metastatic infiltration. Cellient analysis of vitreous specimens had a diagnostic yield of 86.3% in unsolved uveitis cases.